2014
DOI: 10.1371/journal.pone.0094338
|View full text |Cite
|
Sign up to set email alerts
|

Allele-specific Characterization of Alanine: Glyoxylate Aminotransferase Variants Associated with Primary Hyperoxaluria

Abstract: Primary Hyperoxaluria Type 1 (PH1) is a rare autosomal recessive kidney stone disease caused by deficiency of the peroxisomal enzyme alanine: glyoxylate aminotransferase (AGT), which is involved in glyoxylate detoxification. Over 75 different missense mutations in AGT have been found associated with PH1. While some of the mutations have been found to affect enzyme activity, stability, and/or localization, approximately half of these mutations are completely uncharacterized. In this study, we sought to systemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 25 publications
2
25
0
Order By: Relevance
“…Thus, DECA seems to be promising for further studies in animal models. Recently, an additional 75 missense mutations in AGT have been identified, and almost half are uncharacterized (7,29). DECA or similar small molecules may be beneficial for rescuing PH1 caused by these new AGT mutants.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, DECA seems to be promising for further studies in animal models. Recently, an additional 75 missense mutations in AGT have been identified, and almost half are uncharacterized (7,29). DECA or similar small molecules may be beneficial for rescuing PH1 caused by these new AGT mutants.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the purification and characterization of the variants expressed in E. coli are suitable to dissect and quantify the effect of a mutation on the functional properties of AGT as well as on its secondary, tertiary and quaternary structures [11][12][13]17,18,35,36,[51][52][53][54][55][56][57][58]. Yeast and cell-free systems allow a rapid but semi-quantitative determination of the impact of each mutation on the intracellular activity, stability and assembly of the protein [37,53,54,59]. Thus, only the combination of more than one approach can provide a detailed picture of the molecular defect of a pathogenic variant.…”
Section: A Comprehensive Analysis Of the Molecular And Cellular Effecmentioning
confidence: 99%
“…It has been demonstrated that PH1-causing mutations can affect both the thermodynamic and kinetic stability of the protein and decrease the activation free energy for denaturation [17]. Moreover, many studies show that the thermal destabilization of variants associated with the minor allele is exacerbated by the presence of the P11L polymorphism [59]. Additionally, an increased susceptibility to proteolytic cleavage, often observed in the variants, gives important information about conformational changes leading to the exposure of flexible regions [18,59].…”
Section: A Comprehensive Analysis Of the Molecular And Cellular Effecmentioning
confidence: 99%
See 2 more Smart Citations